Long-Term Follow-Up of Patients after Autologous Bone Marrow Cell Infusion for Decompensated Liver Cirrhosis - Kim, Ja Kyung (Cell Transplant, 2017)
Although several human clinical trials using various bone marrow-derived cell types for cirrhotic or decompensated patients have reported a short-term benefit, long-term follow-up data are limited. We analyzed the long-term clinical outcomes of autologous bone marrow cell infusion (ABMI) for decompensated liver cirrhosis (LC). Patients enrolled in a pilot single-armed ABMI study were followed up more than 5 years. Bone marrow-derived mononuclear cells (BM-MNCs) from decompensated LC were harvested and after processing were infused into a peripheral vein. The laboratory test results and long-term clinical course including liver transplantation (LT), development of cancer, cause of death, and survival after ABMI were analyzed. Nineteen patients were followed up for a median of 66 months after ABMI. Liver function, including serum levels of albumin and Child–Pugh (CP) score, was improved at the 1-year follow-up. Liver volume was significantly greater, cirrhosis was sustained, and collagen content was decreased at the 6-month follow-up. Five years after ABMI, five patients (26.3%) maintained CP class A without LT or death, and five patients (26.3%) had undergone elective LT. Hepatocellular carcinoma (HCC) occurred in five patients (26.3%), and lymphoma and colon cancer occurred in one patient each. Three patients (15.8%) were lost to follow-up at months 22, 31, and 33, respectively, but maintained CP class A until their last follow-up. Five patients expired due to infection. While improved liver function was maintained in some patients for more than 5 years after ABMI, other patients developed HCC. Further studies of long-term follow-up cohorts after cell therapy for LC are warranted.